2020
DOI: 10.1039/c9py01508f
|View full text |Cite
|
Sign up to set email alerts
|

Lewis pair catalyzed highly selective polymerization for the one-step synthesis of AzCy(AB)xCyAz pentablock terpolymers

Abstract: A Et3B/DBU pair with a 2/1 feed ratio allowed for the chemoselective control and kinetic control over terpolymerization of epoxides, anhydrides and rac-lactides, affording unique AzCy(AB)xCyAz pentablock terpolymers in a one-step procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Moreover, it was found that the ROAC cycle of PO/PA was faster than the ROP cycle of LA using TEB/DBU, unlike those previously reported. 33 Very recently, based on the ROAC of epoxides and anhydrides catalyzed by alkali metal carboxylates, 34 Satoh et al (2021) successfully employed these environmentally benign catalysts for the switchable ROAC and ROP of various combinations of epoxides, anhydrides, cyclic esters and initiators to achieve sequence-controlled multiblock polyesters with high effectiveness and selectivity. 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was found that the ROAC cycle of PO/PA was faster than the ROP cycle of LA using TEB/DBU, unlike those previously reported. 33 Very recently, based on the ROAC of epoxides and anhydrides catalyzed by alkali metal carboxylates, 34 Satoh et al (2021) successfully employed these environmentally benign catalysts for the switchable ROAC and ROP of various combinations of epoxides, anhydrides, cyclic esters and initiators to achieve sequence-controlled multiblock polyesters with high effectiveness and selectivity. 17…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, lactides were usually used in the self-switchable terpolymerization of epoxides, anhydrides and cyclic esters, while lactones were rarely explored in detail. 17,24,31–33,35 Furthermore, most of the previously reported catalyst systems displayed much lower activity toward terpolymerization when lactones were involved. 16,36 This phenomenon has been attributed to the fact that organic bases could always show much higher activity for ROP of lactides than lactones, and only the usage of stronger organic bases or urea/base pairs shows sufficient kinetic activation for the ROP of δ-valerolactone (VL) and ε-caprolactone (CL).…”
Section: Introductionmentioning
confidence: 99%
“…[13] This elegant approach has been developed, still now, only with few catalytic systems. [14] Notably, among these, also organocatalysts [15] and multinuclear organometallic catalysts [14d,16] have been described.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Zhu et al used H 2 O as the initiator to catalyze the highly selective ROCOP of PO, PA, and rac-LA with TEB/DBU pair to synthesize α,ω-dihydroxy pentablock terpolymers in one pot (Figure 9; Zhu et al, 2020). First, separate catalytic experiments were carried out, and it was found that with TEB/DBU molar ratio being 1:1, the ROCOP of PO/PA showed a moderate catalytic activity and formed a completely alternating poly(trimethylene phthalate).…”
Section: Metal-free Lewis Pair Catalyst Systemmentioning
confidence: 99%